PENGARUH INTERNET FINANCIAL REPORTING DAN TINGKAT PENGUNGKAPAN INFORMASI WEBSITE TERHADAP FREKUENSI PERDAGANGAN SAHAM PERUSAHAAN DI BURSA - Eman Sukanto (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2011)
Internet gives every body in the world more easily, quickly, cheaper and acurately acess to reach the wide geographical area. Business and finance information representation based on internet can be more fleksible and suitable on user needs to support their business decision making.Information technology growth especially internet was impact corporate information representation from traditional to Internet Financial Reporting (IFR). Beside that, there is many companies efforts to reduced the asimetry information by using company’s websites to cast information deal with that company. The research objectives is to knows the effect of the IFR practical and level of website’s information cast on companies stock exchange frequencies. The result showed that IFR and level of website’s information cast has a positif and significant effect on companies stock exchange frequencies.